PENGARUH PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP POLA KOMUNIKASI EFEKTIF MAHASISWA ILMU KOMUNIKASI UNIVERSITAS MUHAMMADIYAH KOTABUMI ANGKATAN 2022 - Wahab Nur Kadri; Ahmad Yoga Dian Andika (Universitas Muhammadiyah Kotabumi, 2022)
The purpose of this research is to see the influence of using social media TikTok on Communication Science students at Muhammadiyah University Kotabumi class of 2022 on communication habits in communicating with their peers. This research method uses quantitative research methods whose main analysis is simple linear regression analysis. This research uses non-probability sampling techniques and purposive sampling design. A questionnaire designed based on key indicators from the two research variables was distributed to 73 active communication science students at Muhammadiyah University, Kotabumi. The results of exploratory data analysis using IBM SPSS Statistics 26 show that the social media variable Tiktok (X) has a significant effect on the communication patterns (Y) of Muhammadiyah University Kotabum students. Meanwhile, Tiktok social media has a significant influence on the communication patterns of Communication Science students at Muhammadiyah University, Kotabumi